Análise das mudanças sócio-econômicas, tecnológicas e ambientais no APL do Açafrão em Mara Rosa e região Goiás (1997 2009) - BORGES, Murilo Sousa (2009)
The municipality of Mara Rosa is located in the state of Goias and is known as the Brazilian capital of turmeric as the largest producer of culture in Goias and Brazil. The activity of turmeric in Mara Rosa received assistance from public and private institutions since 1997, when the executive power of the municipality and the Association of Small Farmers in the region of Pastinho sought the Federal University of Goias to promote the development of the productive chain of turmeric in Goias. In 2004, after the creation of the Permanent Working Group for Local Production, created by the Federal Government, was established the Local Productive Arrangement (LPA) of turmeric in the municipality of Mara Rosa, made possible by the large number of producers of turmeric, in around 300, and the tradition of growing the crop in the region. The objective of this study is to understand the social, technological, economic and environmental changes occurred in LPA turmeric postinstitutional interventions. The theoretical studies were carried out previously directed to agribusiness turmeric authors Milhomem & Teixeira (1998), Marinozzi (2002) and Noronha (2003). The research was based on data collected directly from participants in the agribusiness of turmeric in the region. The survey found that the average yield per hectare had increased up to 50.0% and gross margin achieved by producers in the increased activity of turmeric. The study concludes that the interventions implemented and under implementation in the region have promoted the social, economic and technological producers of turmeric, with the need to adopt new practices in order to preserve the environment